2020
DOI: 10.1021/acsanm.0c02254
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Supported Cobalt Nanoparticles as Catalysts for the Selective Hydrogenation of Nitroarenes to Arylamines and Pharmaceuticals

Abstract: Chemoselective hydrogenation of nitroarenes under industrially viable conditions is one of the attractive reaction for chemical, pharma, and pesticide industries. Herein, we report a reusable, stable, and renewable carbon-supported cobalt nanocatalyst (Co/MA-800) for the chemoselective reduction of structurally diverse nitroarenes with molecular hydrogen. The Co/MA-800 nanocatalyst was prepared via simple and straightforward carbonization of macroalgae and characterized by transmission electron microscopy, X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 52 publications
0
50
0
Order By: Relevance
“…S1A, all XRD patterns show a diffraction peak at 2θ = 26° which is assigned to graphitic carbon [18]. For the monometallic catalysts 2wt%Co@NC-700 and 2wt%Ni@NC-700, two additional weak diffraction peaks at 2θ = 44.5°, 51.8° are observed in the XRD patterns, which are ascribed to the planes (111), ( 200) and (220) of Co 0 and Ni 0 [10,16]. The peaks of Co 0 /Ni 0 phases at 2θ = 44.5°, 51.8° are also found in the patterns of all bimetallic catalyst samples.…”
Section: Catalyst Characterizationmentioning
confidence: 95%
See 1 more Smart Citation
“…S1A, all XRD patterns show a diffraction peak at 2θ = 26° which is assigned to graphitic carbon [18]. For the monometallic catalysts 2wt%Co@NC-700 and 2wt%Ni@NC-700, two additional weak diffraction peaks at 2θ = 44.5°, 51.8° are observed in the XRD patterns, which are ascribed to the planes (111), ( 200) and (220) of Co 0 and Ni 0 [10,16]. The peaks of Co 0 /Ni 0 phases at 2θ = 44.5°, 51.8° are also found in the patterns of all bimetallic catalyst samples.…”
Section: Catalyst Characterizationmentioning
confidence: 95%
“…Recently, catalysts based on non-noble metals, such as Fe [9], Co [10], and Ni [11], have demonstrated high efficiencies in the hydrogenation or reduction of nitroarenes. Meanwhile, the investigations revealed that nitrogendoped carbon materials (NCMs) were excellent supports for enhancing the activity of metal catalysts [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Next, the reduction of nitroarenes is one of the most widely used reaction in chemical industries; the resulting anilines are often found in fragrances, dyestuff, and pharmaceuticals [31b,34] . During one‐shot N ‐methylation of nitroarenes with methanol, the formation of low amounts of anilines was noticed.…”
Section: Resultsmentioning
confidence: 99%
“…Arylamines and their derivatives possess a paramount importance as intermediates for pharmaceuticals and natural products, agrochemicals, conducting polymers (PANI), and dyes in the chemical industry 57 59 . Arylamines are extremely important ligand for the coordination to transition metals 60 .…”
Section: Resultsmentioning
confidence: 99%